2016
DOI: 10.2224/sbp.2016.44.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Conceptualization of Leader–Member Exchange Processes: a Comprehensive Review

Abstract: In this study, I have provided the first review of recent multilevel developments in the leader– member exchange (LMX) literature and identified fruitful areas for future research. After thoroughly reviewing conceptualization and operationalization in the literature, I summarized empirical findings at the dyadic, individual within-team, and team levels. I then addressed confusion in conceptualization and operationalization in the literature. I also suggested additional antecedents, moderators, and outcome var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Noting that LMX and affect-related constructs are relationship-based and nested in interpersonal processes and functional systems at different levels in an organization, we segue to emerging areas for future research using the multilevel perspective, which focuses on within-person, between persons, interpersonal, team and organizational levels of conceptualization in organizations (Ashkanasy, 2003;Ashkanasy & Humphrey, 2011;Connelly & Gooty, 2015;Yammarino et al, 2005). Our review article is thus distinguished from earlier reviews (e.g., Gooty et al, 2010;Paik, 2016;Schriesheim, Castro, & Cogliser, 1999;Yammarino et al, 2005) insofar as we deal with both LMX and affect. Thus we focus in particular on the intertwined nature and characteristics of both concepts by integrating and synthesizing the LMX and affect research (i.e., theoretically and empirically) across multiple levels of analysis (Ashkanasy, 2003;Tse et al, 2015;Yammarino, et al, 2005).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Noting that LMX and affect-related constructs are relationship-based and nested in interpersonal processes and functional systems at different levels in an organization, we segue to emerging areas for future research using the multilevel perspective, which focuses on within-person, between persons, interpersonal, team and organizational levels of conceptualization in organizations (Ashkanasy, 2003;Ashkanasy & Humphrey, 2011;Connelly & Gooty, 2015;Yammarino et al, 2005). Our review article is thus distinguished from earlier reviews (e.g., Gooty et al, 2010;Paik, 2016;Schriesheim, Castro, & Cogliser, 1999;Yammarino et al, 2005) insofar as we deal with both LMX and affect. Thus we focus in particular on the intertwined nature and characteristics of both concepts by integrating and synthesizing the LMX and affect research (i.e., theoretically and empirically) across multiple levels of analysis (Ashkanasy, 2003;Tse et al, 2015;Yammarino, et al, 2005).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…For example, Henderson et al (2008) and Ma and Qu (2010) found the positive effect of LMX differentiation on behavioural outcomes. The current study has also answered the call of Paik (2016), who suggested exploring more moderators of relative LMX-outcome relationships. This study's findings show that LMXSC is an important element in forming the follower's relational identification and subsequent outcomes.…”
Section: Discussionmentioning
confidence: 54%
“…In the LMXD literature, researchers have demonstrated that the direct effects of LMXD on employee work outcomes are inconsistent and weak (for reviews, see Martin et al [2018] and Paik [2016]). For example, some reported positive effects of LMXD on in-role performance (Haynie et al, 2014) andcommitment (Le Blanc &González-Romá, 2012).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…As prior LMXD studies have centered on team-focused explanations on LMXD phenomena, current knowledge on individual variations in a high LMXD situation is relatively limited (Epitropaki et al, 2016;Paik, 2016).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation